2013
DOI: 10.1016/j.diagmicrobio.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A new factor influencing pathogen detection by molecular assay in children with both mild and severe hand, foot, and mouth disease

Abstract: This study aimed to find novel information concerning pathogen detection and some probable coinfection factors in hand, foot, and mouth disease (HFMD). In this study, 1104 clinically diagnosed HFMD patients were included. Enterovirus 71 (EV71), coxsackievirus A16 (CA16), and 14 different respiratory pathogens were examined from nasopharyngeal swabs using polymerase chain reaction (PCR) or reverse transcriptase PCR (RT-PCR). To evaluate the immune activation in HFMD patients, 8 cytokines and IgM antibodies to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The age distribution of HFMD cases in Asia, compiled from a variety of sources including surveillance and cohort data, is summarized in Figure 5. Data from China [12][13][14]34,[49][50][51][52]94,[100][101][102][103][105][106][107] and Taiwan 5,6,73,108-111 are particularly abundant. Other sources include Hong Kong, 17,18 India, 76,80 Japan, 56,112 Korea, 54,95 Malaysia, 84,113 Singapore, 4,27,88 Thailand 22,23 and Vietnam.…”
Section: Age Distribution Of Hfmd Casesmentioning
confidence: 99%
“…The age distribution of HFMD cases in Asia, compiled from a variety of sources including surveillance and cohort data, is summarized in Figure 5. Data from China [12][13][14]34,[49][50][51][52]94,[100][101][102][103][105][106][107] and Taiwan 5,6,73,108-111 are particularly abundant. Other sources include Hong Kong, 17,18 India, 76,80 Japan, 56,112 Korea, 54,95 Malaysia, 84,113 Singapore, 4,27,88 Thailand 22,23 and Vietnam.…”
Section: Age Distribution Of Hfmd Casesmentioning
confidence: 99%
“…One is compartmental differential equation model [8][9][10][11][12][13][14][15], which is important to understand the spread dynamics of HFMD among the susceptible populations and to enable policy makers to take effective measures to curb the disease spread and reduce the adverse impact of the disease [9,10]. The other is statistical models which can help us find novel information concerning pathogen detection and some probable coinfection factors in HFMD and have been applied to understand HFMD's spatiotemporal transmission and discover the relationship between HFMD occurrence and climate [3,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Of them, Hu et al [4] explored the spatial association of HFMD incidence with several potential determinants and found that child population density and climate factors are potential determinants of the HFMD incidence in most areas in China.…”
Section: Introductionmentioning
confidence: 99%
“…55 Zhu, et al reported that the detection efficiency of EV71 and CA16 was lower in severe HFMD cases by RT-PCR; thus, simultaneous detection of IgM antibodies needs to be considered. 56 However, human enterovirus genes have relatively high homogeneity and there may be some common antigenic sites among different enteroviruses.…”
Section: Serological Diagnosismentioning
confidence: 99%